2023
DOI: 10.3390/ijms24076037
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antibiotic Resistance Genes Identified by Functional Gene Library Screening in Stenotrophomonas maltophilia and Chryseobacterium spp. Bacteria of Soil Origin

Abstract: As one of the most diverse habitats of microorganisms, soil has been recognised as a reservoir of both antibiotics and the antibiotic resistance genes (ARGs). Bacteria naturally inhabiting soil or water often possess innate ARGs to counteract the chemical compounds produced by competitors living in the same environment. When such bacteria are able to cause infections in immunocompromised patients, their strong innate antibiotic resistance mechanisms make treatment difficult. We generated functional gene librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Antibiotic resistance gene predictions showed that herbae pc1-10 T contained two antibiotic resistance genes: IND-4, which is a beta-lactamase found in Chryseobacterium indologenes, and AdeF, which is the membrane fusion protein of the multidrug efflux complex AdeFGH; the proteincoding information is provided by CARD [59] (https://card.mcmaster.ca/ accessed on 21 May 2023). According to a study, bacteria that live in soil or water naturally have ARGs that they can use to compete with other organisms that share the same habitat [60]. We used CRISPRCasFinder [61] to identify CRISPR (clustered regularly interspaced short palindromic repeats) arrays; 5 of the 23 analysis sequences were found to contain CRISPR but no Cas genes were found in the vicinity of CRISPRs.…”
Section: Genome Analysesmentioning
confidence: 99%
“…Antibiotic resistance gene predictions showed that herbae pc1-10 T contained two antibiotic resistance genes: IND-4, which is a beta-lactamase found in Chryseobacterium indologenes, and AdeF, which is the membrane fusion protein of the multidrug efflux complex AdeFGH; the proteincoding information is provided by CARD [59] (https://card.mcmaster.ca/ accessed on 21 May 2023). According to a study, bacteria that live in soil or water naturally have ARGs that they can use to compete with other organisms that share the same habitat [60]. We used CRISPRCasFinder [61] to identify CRISPR (clustered regularly interspaced short palindromic repeats) arrays; 5 of the 23 analysis sequences were found to contain CRISPR but no Cas genes were found in the vicinity of CRISPRs.…”
Section: Genome Analysesmentioning
confidence: 99%